ظاهرة اختلاف العلماء المعاصرين في تأويل النصوص القرآنية والحديثية = The phenomenon of Differences of Contemporary Scholars of Islam in Interpreting the Texts of the Quran and Hadith - Subhani, Zulqernain Haider; Ali, Mohammed Farid (IIUM, 2021)
The differences of opinions among scholars of Islam are nothing new rather they have been part of Islamic tradition since the very beginning until now. However, there has always been a major part of Islamic tradition on which most of the scholars agreed and that was considered as the position of the majority (Jamhoor) and that part had gained a kind of sacredness and impermissibility for scholars to differ on it. It is also to be noted here that there have also been some instances of disagreements from the majority in the history of Islamic tradition though such instances were very few in numbers. Therefore, the phenomenon which we are referring to in this study is the phenomenon of disagreements of contemporary scholars on a particular issue from what has been considered as the stance of the majority or consensus and these scholars form a new majority or consensus in our time and this is something which seems unique to modern time and absent in the history of Islamic tradition. Among examples indicating to this phenomenon are the issues of triple Talaq, stoning, punishment on apostasy, the condition of Quraish lineage for a ruler or Khalifa, the issue of leadership of women, the issue of magic on the Prophet and the issue of abrogation in the Quran and so on. This study is very significant as it presents a phenomenon in relation to Islamic tradition, more particularly, to the interpretations of the texts of the Quran and Hadith. And this phenomenon is quite new and has very strong impact on contemporary thoughts. The objective of this study is to present this new phenomenon of our tradition by studying few issues from the works of contemporary scholars of Islam. Content analysis and inductive methods have been used in this paper. As a conclusion the study promotes the flexibility and resilience in matters of differences, and it presents the ways of academic differences and its forms in contemporary scholarship.